Parallelization of a Stellarator Simulation Code in Plasma Physics - Chavarría, Luis Diego (2019)
There are multiple applications of plasma. To better understand the fundamental characteristics of plasma, physicists at Costa Rica Institute of Technology built a plasma confinement device, code named SCR-1. This device was paired with a simulation code. The computer program emulates the dynamics of plasma as it is confined within SCR-1. This program is computationally intensive. To alleviate the performance demand, it was necessary to apply high performance computing machinery. In this paper we present the work on improving the performance of the this application by implementing vectorization and paral- lelism through distributed and shared memory. We also include experimental results that display acceleration factors higher than 30X. Additionally, we show speedup results for weak and strong scaling experiments.